Third-trimester Spontaneous Rupture of an Unscarred Uterus with Massive Intra-abdominal Hemorrhage During Tocolysis in a Pregnant Woman who has had Multiple Instrumental Abortions - Yi-Hui Lin; Chih-Ping Chen; Jen-Ru Lin; Li-Fan Yeh; Tze-Chien Chen (Elsevier, 2004)
Objective: Uterine rupture is a rare and catastrophic event. We present a case of spontaneous rupture in an unscarred uterus with massive internal bleeding during tocolysis in the third trimester. Case Report: A 31-year-old woman, gravida 5, para 2, was admitted to our hospital at 32 weeks of gestation because of lower abdominal pain, fever, and chills. She had no history of gynecologic surgery except for two suctional dilatation and curettage procedures because of intrauterine fetal death. Her husband was a balanced reciprocal translocation carrier. On admission, cardiotocography (CTG) showed irregular uterine contractions, and an intravenous beta-sympathomimetic agent was given along with antibiotics. Following the medication, maternal tachycardia was observed without any obvious change in blood pressure. One hour after the treatment, however, CTG showed persistent moderate variable decelerations of fetal heart beats and a decrease in maternal blood pressure. Emergency cesarean section was performed under the impression of acute fetal distress. A 1 cm laceration over the left uterine cornus was noted, with active bleeding and hemoperitoneum of 1,500 mL. A male baby weighing 2,250 g was delivered; his Apgar scores at 1 and 5 minutes were 1 and 5, respectively. Primary repair of the uterus was performed. The postoperative course was uneventful. The infant was doing well at age 2 months. Conclusion: The present case provides evidence that spontaneous rupture of an unscarred uterus may occur during tocolytic management in the third trimester in pregnant women with a history of multiple instrumental abortions. We suggest that the feto-maternal condition be closely monitored during tocolytic management of such patients. Any change in the vital signs of the mother as well as the fetus should alert one to the possibility of spontaneous uterine rupture.